Motion planning and control of cooperating robotic systems in orbit - Rekleitis, Georgios (Σχολή Μηχανολόγων Μηχανικών, 2015)
Both interplanetary traveling crafts and stationary systems will be in need of servicing, such as assembly, maintenance, replacement of broken/expendable modules, refueling, inspection and repair. To relieve astronauts from dangerous extra-vehicular activities, enhance performance and extend the feasible tasks range, the international research community has been focusing on the realization of autonomous robotic servicing. While important tasks, such as orbital assembly and debris handling, require passive object handling capabilities, the actual handling of a secured passive object by a number of free-flying robotic servicers, has not been studied adequately, with several issues still open. On-orbit object handling has similarities to cooperative manipulation of passive objects on earth, with the additional complexities that in space no fixed ground to support the manipulators exists, thus letting momentum changes to play a key role in body motion. One more issue arises from the fact that orbital system thrusters are of on-off control nature. In order to protect the thruster valves from the extreme space conditions, proportional or pulse-width-modulation (PWM) thrusters are not used in space, at least not as PWM is used on terrestrial systems, thus reducing system positioning capabilities, when only thrusters are used. The introduction of a number of manipulator-equipped free-flying servicers, where both on-off thruster propulsion and manipulator continuous forces/ torques are used for passive object handling, both for the case of firm grasp and in the more general case of point contact, between the servicer manipulator end-effectors and the passive object, is presented in this thesis. The design of a controller for the free-flying servicer manipulators that enables the stable handling of the passive object by the servicers, in trajectory tracking scenarios, as well as the design of a controller for the free-flying servicer bases that enables them to move within the workspace of their manipulators, under the influence of the reaction generalized forces from their manipulator bases, is also presented. An initial comparison between the choice of three small free-flying robotic servicers and a single, larger one is also conducted. A spatial system of robotic servicers handling a passive object is highly non-linear. Unfortunately, there is not much generally applied theory on the field of non-linear system robustness. One method is to use linearization, under certain assumptions, in order to be able to use linear systems robustness tools. The sensitivity of the controller for the 3D motion of the handled passive object in space in terms of parameter estimation is also studied in this work. Finally, the design of a two-layer optimization process that allows for i) optimal selection of contact points between the manipulator end-effectors and the passive object, for both contact cases and ii) force distribution so that the required control generalized force for the passive object motion, is applied by the manipulator end-effectors, is also presented.